Service, Taste, and Trust: Driving Purchase Decisions in Premium Japanese Restaurants - Nabila, Anugrah Putri; Sutarjo, Sutarjo; Prastowo, Sugeng (International Journal of Business, Law, and Education, 2025)
This study aims to examine how the service quality, taste quality, and the restaurant's atmosphere affect customers' buying choices at Sushi Tei Karawaci. It also examines how consumer trust plays a role in connecting these factors, and how Islamic business ethics can influence these relationships. The research uses a quantitative method along with SEM-PLS analysis. The findings show that service quality and taste quality have a strong effect on consumer trust, but the restaurant's atmosphere does not. Taste quality and the atmosphere strongly influence purchasing decisions, but service quality does not. Consumer trust is a big factor in purchasing decisions and also helps connect the other factors. Islamic business ethics affect how service quality, taste quality, and the atmosphere relate to purchasing decisions. Honesty, fairness, and transparency, which are part of Islamic ethics, make these connections stronger. The study suggests that restaurant owners should focus on improving service and taste, build trust with customers, and use Islamic ethical values as part of their marketing plan to be more responsible and effective.